1979
DOI: 10.1210/jcem-48-1-114
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Melatonin in Man: Episodic Secretion throughout the Light-Dark Cycle

Abstract: A sensitive and specific RIA for melatonin has been validated for human plasma. Five young adult men had plasma samples obtained every 20 min during two 24-h periods. One was a normal active period and the other a basal period with complete bed rest. Melatonin was found to be secreted episodically throughout the 24 h in each condition, with secretory episodes clearly present during the waking day in the presence of bright light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 19 publications
5
34
1
Order By: Relevance
“…The amplitude in salivary melatonin secretion was decreased in pregnant women with complications in the third trimester in the present study and was likely because melatonin decreases after awaking, upon light exposure (12), or when sleep is shallow (39), and the sleep state often becomes shallow by polysomnography in the third trimester (40).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The amplitude in salivary melatonin secretion was decreased in pregnant women with complications in the third trimester in the present study and was likely because melatonin decreases after awaking, upon light exposure (12), or when sleep is shallow (39), and the sleep state often becomes shallow by polysomnography in the third trimester (40).…”
Section: Discussionmentioning
confidence: 52%
“…Pregnant women with hypertensive or glucose metabolic disorder complications had smaller circadian variation in salivary melatonin secretion, and their values were lower throughout the day than healthy pregnant women. (12). Melatonin is thus a humoral factor that transmits information to maintain biorhythms, such as the sleep-wake rhythm (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weinberg et al (1979) found that keeping young men at bed rest in a fixed light/dark cycle had no effect on mean daytime or nocturnal melatonin as compared to levels seen with usual daily activities. Strenuous activities were not discussed in that report.…”
Section: Benzcdiazepinesmentioning
confidence: 80%
“…Vaughan et al, (1976) and Weinberg et al, (1979) reported that having subjects sleep during the usual light period did not cause an increase in melatonin. However, lights were on during sleep in "those studies.…”
Section: I* I00mentioning
confidence: 99%